Choose Your Own Marine Energy Adventure Game: Collision Risk (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The risk of collision between marine animals (marine mammals, pelagic fish, and diving seabirds) and underwater turbines continues to be the first question raised by regulators for new tidal or riverine energy projects around the world, and the most significant issue that slows down consenting/permitting. The challenges to understanding collision risk stem from the difficulty in observing close encounters and interactions of marine animals with a tidal or riverine turbine, which rotates much slower than a hydroelectric turbine or a boat propeller. To better understand this risk, the marine energy community and the general public need to be educated on the processes and various stages involved in collision risk of marine animals with turbines. This project aimed to develop an interactive outreach tool for the marine energy community and the general public, to educate the audience on the low risk of collision by highlighting the different stages of a collision event at various spatial scales and featuring a fish species of concern, the Atlantic salmon. This tool is a three-dimension educational interactive experience, accessible from any web-connected platform, and is hosted on a publicly accessible website. Throughout the experience, the player is presented with various decisions to take as the salmon approaches and interacts with a tidal turbine. At each step along the way, the player is provided with bite-size scientific information and weblinks to deepen their understanding of the topic. This short but efficient tool with expert messages is a "hands-on" experience for the players, where they are the animals and make the decisions leading up, or not, to collisions. The outcomes of this project will support broad outreach and education goals in order to reduce barriers to consenting/permitting for future deployment of tidal and riverine turbines.